2022
DOI: 10.1038/s41591-022-01932-x
|View full text |Cite
|
Sign up to set email alerts
|

Artificial intelligence-enabled detection and assessment of Parkinson’s disease using nocturnal breathing signals

Abstract: There are currently no effective biomarkers for diagnosing Parkinson’s disease (PD) or tracking its progression. Here, we developed an artificial intelligence (AI) model to detect PD and track its progression from nocturnal breathing signals. The model was evaluated on a large dataset comprising 7,671 individuals, using data from several hospitals in the United States, as well as multiple public datasets. The AI model can detect PD with an area-under-the-curve of 0.90 and 0.85 on held-out and external test set… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
54
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 124 publications
(69 citation statements)
references
References 54 publications
0
54
0
Order By: Relevance
“…At the time of the writing, the radio device used in this paper is incorporated in a large number of clinical studies in neurological diseases ( 77 , 78 ), immune diseases ( 79 , 80 ), and rare diseases ( 75 , 81 ). Some of these studies involve over 250 devices, and many of them run for several years.…”
Section: Methodsmentioning
confidence: 99%
“…At the time of the writing, the radio device used in this paper is incorporated in a large number of clinical studies in neurological diseases ( 77 , 78 ), immune diseases ( 79 , 80 ), and rare diseases ( 75 , 81 ). Some of these studies involve over 250 devices, and many of them run for several years.…”
Section: Methodsmentioning
confidence: 99%
“…As the RMSE of 6.01 in predicting the total MDS-UPDRS score by our predictive model is lesser than the inherent noise of 8.059 in the instrument itself, it is safe to assume that the performance of the predictive model is acceptable for real-world applications. Moreover, as per the recent study [26][27] in predictive modeling of PD using imaging genetics on a combination of DNA genotyping and neuroimaging, the authors reported an RMSE of 7.82 in predicting MDS-UPDRS-Score.…”
Section: Discussionmentioning
confidence: 68%
“…For these behavioral states (e.g., sleep), a significant deviation in the breathing pattern may predict underlying pathological conditions as shown in a recent study on patients with Parkinson’s disease. 47 …”
Section: Discussionmentioning
confidence: 99%